2008
DOI: 10.1002/polb.21458
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and properties of cyanate ester/liquid polyurethane/silica nanocomposites

Abstract: The high‐speed homogeneous shearing method was applied to prepare nanocomposites of cyanate ester (CE) with liquid polyurethane elastomer (PUR) and silica. To investigate the influence of various components on the morphology and properties of the ternary composites, the binary composites of CE/PUR and CE/silica were also involved in this article. The morphology of the cured materials of binary and ternary systems was investigated by transmission electron microscopy (TEM), and the results show that silica nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…A strategy used to provide thermooxidative protection in cyanurate polymer networks that has been explored through much recent investigation is the incorporation of silicon or siloxy moieties in the form of monomers and cocuratives, blends and modifiers, silica nanoparticles, clay nanoplatelets, or other silicon‐containing nanostructures including oligomeric silsesquioxanes . While the addition of silicon in fully oxidized form (i.e., as SiO 2 ) can provide an in‐place barrier to oxygen permeation, the use of unoxidized organosilicon moieties or partly oxidized silicates allows for the in situ generation of a protective barrier during high‐temperature oxidation or exposure to energetic forms of oxygen (such as atomic oxygen in low Earth orbit) .…”
Section: Introductionmentioning
confidence: 99%
“…A strategy used to provide thermooxidative protection in cyanurate polymer networks that has been explored through much recent investigation is the incorporation of silicon or siloxy moieties in the form of monomers and cocuratives, blends and modifiers, silica nanoparticles, clay nanoplatelets, or other silicon‐containing nanostructures including oligomeric silsesquioxanes . While the addition of silicon in fully oxidized form (i.e., as SiO 2 ) can provide an in‐place barrier to oxygen permeation, the use of unoxidized organosilicon moieties or partly oxidized silicates allows for the in situ generation of a protective barrier during high‐temperature oxidation or exposure to energetic forms of oxygen (such as atomic oxygen in low Earth orbit) .…”
Section: Introductionmentioning
confidence: 99%
“…Taha and Gao 8 investigated the effects of fumed silica content on the thermal and dielectric properties of BCE resins, and results showed that the addition of fumed silica could effectively improve the thermal and dielectric properties of BCE resin. Zhang et al 20 investigated the morphology and properties of cyanate/liquid polyurethane/silica composites, and results showed that the silica was uniformly distributed in the matrix, and the composites displayed higher fracture toughness and impact strength compared with other binary systems.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al. 20 investigated the morphology and properties of cyanate/liquid polyurethane/silica composites, and results showed that the silica was uniformly distributed in the matrix, and the composites displayed higher fracture toughness and impact strength compared with other binary systems.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to polymeric matrix, thermosetting resins exhibit unique advantages on the processing characteristics over thermoplastics. 30,31 Cyanate ester (CE) resin offers advantages as the composite matrix owing to its outstanding thermal stability, excellent dielectric property, high mechanical property, good moisture and radiation resistance; hence it is widely regarded as the right candidate with the great potential to prepare structural/functional materials of this century. 32,33 However, unfortunately, no literature discusses the preparation and characterization of ZrO 2 /CE composites.…”
Section: Introductionmentioning
confidence: 99%